(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2021)
Skin permeability of Sevan trout has been studied during 30 min in different solutions: in distilled water, in 70% ethanol, in solution of 0.125 M KCl. The permeability was measured by methylene blue. It was shown that the skin permeability for this dye changes depending in what solution these shreds of Sevan trout were kept and from which side the shred was tightened. It was also shown that distilled water, solution of 0.125 M KCl and ethanol cause structural changes in the skin layers of the Sevan trout, in particular the epidermis.